Dermatoglyphics and coronary artery disease - Liu, Yage (1990)
Results of the analysis of qualitative and quantitative characteristics of dermatoglyphics of the digito-palmar complex in 84 male examinees with coronary artery disease and a control group of 200 healthy male examinees is presented. Descriptive analyses reveal signifiant differences between the two groups in the frequencies of patterns in the thenar/first interdigital area, hypothenar area and second, third and fourth interdigital areas. In quantitative traits, statistically significant differences were found only in the palmar areas, where ridge counts and atd angle are lower in CAD patients than in the control group. Canonical discriminant analysis enabled the correct classification between the group of CAD patients and control group in 74.3% examinees. These resultssuggest a potential relationship between coronary artery disease and
qualitative and quantitative palmar dermatoglyphic traits, which can be used for the identification of a high CAD risk group in medical practice
Bibliografija: 24 jed.
Keywords: Dermatoglifi; Kardiovaskularni sustav -- Bolesti; Muškarci